2000
DOI: 10.1002/1529-0131(200005)43:5<1016::aid-anr9>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Single values of serum transferrin receptor and transferrin receptor ferritin index can be used to detect true and functional iron deficiency in rheumatoid arthritis patients with anemia

Abstract: The results of this study elucidate the roles of sTfR and the TfR-F Index in the differential diagnosis between IDA and ACD and provide direct evidence that these parameters are useful in detecting FID, irrespective of the concurrent iron storage status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
2
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 16 publications
4
53
2
3
Order By: Relevance
“…Prior studies have suggested that the sTfR Index may improve the ability to accurately classify anemia in diseases with active inflammation [5,[15][16][17][18]. However, these studies involved single institutions with a limited number of subjects reflecting the specialized patient population at that center, which can introduce possible bias in study outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have suggested that the sTfR Index may improve the ability to accurately classify anemia in diseases with active inflammation [5,[15][16][17][18]. However, these studies involved single institutions with a limited number of subjects reflecting the specialized patient population at that center, which can introduce possible bias in study outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The sTfR Index thus takes advantage of the reciprocal relationship between two variables influenced by iron deficiency, an increase in sTfR and a decrease in the ferritin concentration. While sTfR and ferritin measurements are useful in the diagnosis of iron deficiency and in the differential diagnosis of various types of anemia, some reports have suggested that the combination of sTfR and ferritin measurements and the calculation of the sTfR Index improves the ability to accurately classify anemia, particularly in anemia accompanying diseases with active inflammation [5,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have reported that mean sTfR levels were uninfluenced by conditions of chronic inflammatory diseases in adults, thus reflecting the true iron status of the individual (Ferguson et al, 1992;Suominen et al, 2000). In parasitic infections like malaria, Kuvibidila et al (1995) found sTfR levels to reflect the true iron status of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…Values of sTfR decrease after adequate iron supplementation, independently of marrow iron stores, indicating that they are good indicators of functional iron deficiency [90]. Contrarily to serum ferritin, sTfR may thus prove to be a diagnostic test of iron deficiency in patients with inflammation.…”
Section: Soluble Tfr and Inflammationmentioning
confidence: 99%